Read me / Anchieta Ave Avillanova...[et.al.]; editor, Barli Bram, Retno Muljani - Anchieta Ave Avillanova ; Barli Bram ; Retno Muljani (Sanata Dharma Univeristy Press, 2017)
(vi), 132 halaman : ilustrasi, foto ; 21 cm